Current status of clinical trial research and application of immune checkpoint inhibitors for non-small cell lung cancer - Wang, Fuli; Xia, Teng; Li, Zhiqiang; Gao, Xuzhu; Fang, Xinjian (Frontiers in Oncology, 2023)
Immunotherapy has emerged as a hot topic in the treatment of non-small cell lung cancer (NSCLC) with remarkable success. Compared to chemotherapy patients, the 5-year survival rate for immunotherapy patients is 3-fold higher, approximately 4%-5% versus 15%-16%, respectively. Immunotherapies include chimeric antigen receptor T-cell (CAR-T) therapy, tumor vaccines, immune checkpoint inhibitors, and so forth. Among them, immune checkpoint inhibitors are in the spotlight. Common immune checkpoint inhibitors (ICIs) currently in clinical use include programmed death receptor-1(PD-1)/programmed death ligand-1(PD-L1) and cytotoxic T lymphocyte-associated antigen 4(CTLA-4). This article focuses on monotherapy and combination therapy of CTLA-4 and PD-1/PD-L1 immune checkpoint inhibitors. In particular, the combination therapy of ICIs includes the combination of ICIs and chemotherapy, the combination therapy of dual ICIs, the combination of ICIs and anti-angiogenic drugs, the combination of ICIs and radiotherapy, and the combination of ICIs inhibitors and tumor vaccines and so forth. This article focuses on the combination therapy of ICIs with chemotherapy, the combination therapy of dual ICIs, and the combination therapy of ICIs with antiangiogenic drugs. The efficacy and safety of ICIs as single agents in NSCLC have been demonstrated in many trials. However, ICIs plus chemotherapy regimens offer significant advantages in the treatment of NSCLC with little to no dramatic increase in toxicity, while combined dual ICIs significantly reduce the adverse effects (AEs) of chemotherapy. ICIs plus anti-angiogenic agents regimen improves anti-tumour activity and safety and is expected to be the new paradigm for the treatment of advanced NSCLC. Despite some limitations, these agents have achieved better overall survival rates. In this article, we review the current status and progress of research on ICIs in NSCLC in recent years, aiming to better guide the individualized treatment of NSCLC patients.